ON FRIENDSHIP – CICERO VS. JOHN OF SALISBURY - Oana-Corina FILIP (Studia Universitatis Babeș-Bolyai. Philosophia, 2017)
On Friendship – Cicero vs. John of Salisbury. On the topic of friendship, a clear filiation can be traced between Cicero and John of Salisbury. However, it is not a mere quotation, but an organic evolution of thought. For both philosophers, friendship appears as supporting social and political relations, thus making the existence of the commonwealth possible. Their views on the different characteristics of friendship are at the same time both shared and different, thus tracing a development of the concept.